Hypothermic Cardiac Arrest – Retrospective cohort study from the International Hypothermia Registry. (October 2021) - Walpoth, Beat H.; Maeder, Monika Brodmann; Courvoisier, Delphine S.; Meyer, Marie; Cools, Evelien; Darocha, Tomasz; Blancher, Marc; Champly, Frédéric; Mantovani, Lorenzo; Lovis, Christian; Mair, Peter
Abstract: Aim: The International Hypothermia Registry (IHR) was created to increase knowledge of accidental hypothermia, particularly to develop evidence-based guidelines and find reliable outcome predictors. The present study compares hypothermic patients with and without cardiac arrest included in the IHR. Methods: Demographic, pre-hospital and in-hospital data, method of rewarming and outcome data were collected anonymously in the IHR between 2010 and 2020. Results: Two hundred and one non-consecutive cases were included. The major causeof hypothermia was mountain accidents, predominantly in young men. Hypothermic Cardiac Arrest (HCA) occurred in 73 of 201 patients. Core temperature was significantly lower in the patients in cardiac arrest (25.0 vs. 30.0 °C, p  < 0.001). One hundred and fifteen patients were rewarmed externally (93% with ROSC), 53 by extra-corporeal life support (ECLS) (40% with ROSC) and 21 with invasive internal techniques (71% with ROSC). The overall survival rate was 95% for patients with preserved circulation and 36% for those in cardiac arrest. Witnessed cardiac arrest and ROSC before rewarming were positive outcome predictors, asphyxia, coagulopathy, high potassium and lactate negative outcome predictors. Conclusions: This first analysis of 201 IHR patients with moderate to severe accidental hypothermia shows an excellent 95% survival rate for patients with preserved circulation and 36% for HCA patients. Witnessed cardiac arrest, restoration of spontaneous circulation, low potassium and lactate and absence of asphyxia were positive survival predictors despite hypothermia in young, healthy adults after mountaineering accidents. However, accidental hypothermia is a heterogenous entity that should be considered in both treatment strategies and prognostication.